Analysis of the plug-in hybrid electric vehicle for the smart grid of Canada - Islam, Mazharul (Taylor & Francis, 2013)
The conventional electricity grids, which are supposed to supply the electricity to the plug-in hybrid electric vehicles (PHEVs), need to adapt to overcome the problems of reliability, security, economics and environmental concerns. Accordingly, electric utilities in several countries are exploring the possibilities of implementing more robust interactive smart grids. This article analyses salient features of a smart grid in the Canadian perspective, and discusses PHEV and its role in the future smart grid. A simulation tool has been used to assess the impacts of charging of PHEV on the future electricity grid of Canada under different penetration rates. The article indicates the associated environmental benefits of PHEV. © 2013 Taylor & Francis.